Management of Convergence Networks and Services 9th Asia-Pacific Network Operations and Management Symposium, APNOMS 2006, Busan, Korea, September 27-29, 2006, Proceedings - Kim, Young-Tak; Takano, Makoto (Computer Communication Networks and Telecommunications,, 2006)
th We are delighted to present the proceedings of the 9 Asia-Pacific Network Operations and Management Symposium (APNOM S2006) which was held in Busan, Korea, on September 27-29, 2006. Recently, various convergences in wired and wireless networks and convergence of telecommunications and broadcastings are taking place for ubiquitous multimedia service provisioning. For example, broadband IP/MPLS wired networks are actively converged with IEEE 802.11e wireless LAN, IEEE 802.16 Wireless MAN, 3G/4G wireless cellular networks, and direct multimedia broadcast (DMB) networks. For efficient support of service provisioning for ubiquitous multimedia services on the broadband convergence networks, well-designed and implemented network operations and management functions with QoS-guaranteed traffic engineering are essential. The Organizing Committee (OC) made the timely selection of "Management of Convergence Networks and Services" as the theme of APNOMS 2006. Contributions from academia, industry and research institutions met these challenges with 280 paper submissions, from which 50 high-quality papers were selected for technical sessions as full papers, and 25 papers as short papers. The diverse topics in this year's program included management of ad-hoc and sensor networks, network measurements and monitoring, mobility management, QoS management, management architectures and models, security management, E2E (end-to-end) QoS and application management, management experience, NGN (next-generation network) management, and IP-based network management.